Determining the Impact of Demographics on the Intention to Leave of Academicians in HEIs of the DCs Like Pakistan (Global Journal of Management and Business Research, 2013)
The main objective of this 'Review Article' was to determine the demographic impact on the Intention to leave of academicians in the higher educational institutions of the developing countries (DCs). The development and achi-evements of any institution generally depends upon its workforce. So that, ITL is the major challenge for HEIs and has some lasting effects in this regard. It is vital for the education sector to have information of the impact of some demographic variables on the employee's ITL for the improvement in the professional and academic status of the academicians. Employee's ITL is one of the major concerns for HEIs among many others. Number of studies has already been conducted to recognize the various dimensions of the ITL. The purpose of the current research is to investigate the impact of demographic variables on the ITL among the academicians. In this study, we developed a "Theoretical Framework", in which the demographics (age, gender, marital status, qualification, designation, department, domicile and experience) were the independent variables and intention to leave was the dependent variable.
Keywords: demographics (age; gender; marital status; designation and educational level); it; heist; academicians